(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The materials of the dominant species and the state of the artificial wood investigation in the conditions of the south steppe zone of Ukraine (Kherson and Mykolaiv regions) are given in the article. It is shown that the best forest species for artificial woods is Gleditsia triacanthos L. The trees of this species in comparison with other species are more high, better take root, grow faster, have less fall, decorative, melliferous, rarely subject to infection and vermin, long-term, especially when the density of trees meet the biological potential of the species. In the zone of chestnut soils G. triacantos is the only species able to create field-protective plantation.